USM RESEARCH PRODUCT “NUTRI MUSH” BAGS FIRST PLACE IN RUSSIAN HALAL EXPO - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 17 June 2015 – Universiti Sains Malaysia (USM) once again made history when a research product of lecture and researcher from the School of Health Sciences, Associate Professor Dr. Wan Rosli Wan Ishak garnered First Place in the Moscow International Halal Exhibition, held from 2123 May 2015 at the Crocus Expo International Exhibition Centre Russia.